Functions of Arginase Isoforms in Macrophage Inflammatory Responses: Impact on Cardiovascular Diseases and Metabolic Disorders - Yang, Zhihong; Ming, Xiu-Fen (Frontiers in Immunology, 2014)
Macrophages play a paramount role in immunity and inflammation-associated diseases, including infections, cardiovascular diseases, obesity‐associated metabolic imbalances and cancer. Compelling evidence from studies of recent years demonstrates that macrophages are heterogeneous and undergo heterogeneous phenotypic changes in response to microenvironmental stimuli. The M1 Killer type response and the M2 Repair type response are best known, and are two extreme examples. Among other markers, inducible nitric oxide synthase (iNOS) and type-I arginase (Arg-I), the enzymes that are involved in L-arginine/nitric oxide (NO) metabolism, are associated with the M1 and M2 phenotype, respectively, and therefore widely used as the markers for characterization of the two macrophage phenotypes. There is also a type-II arginase (Arg-II) which is expressed in macrophages and prevalently viewed as having the same function as Arg-I in the cells. In contrast to Arg-I, little information on the role of Arg‐II in macrophage inflammatory responses is available. Emerging evidence, however, suggests differential roles of Arg-I and Arg-II in regulating macrophage functions. In this article, we will review recent developments on the functional roles of the two arginase isoforms in regulation of macrophage inflammatory responses by focusing on their impact on the pathogenesis of cardiovascular diseases and metabolic disorders.